Acidic pretreatment as a chemical approach for enhanced Photorhabdus temperata bioinsecticide production from industrial wastewater. (15th January 2021) - Jallouli, Wafa; Keskes, Sahar; Guidara, Wassim; Rezgui, Fatma; Sayadi, Sami; Tounsi, Slim
Abstract: The chemical treatment of the wastewater used for the bioinsecticide production by the bacterium Photorhabdus temperata was investigated in this study. An improvement of the volatile suspended solids (VSS) solubilization along with an increase in protein, carbohydrate, reducing sugar and nitrogen concentrations were demonstrated after alkali and thermo-alkali hydrolysis. In contrast, the application of acidic and thermo-acidic pretreatments reduced the organic matter hydrolysis. Compared to untreated wastewater, the chemical oxygen demand (COD) solubilization and the heavy metal concentration, except manganese, were enhanced in all the chemically pretreated wastewaters. Although its low contribution in the solubilization of the wastewater organic matter, the acidic-pretreated wastewater showed the highest performance in supporting P. temperata biopesticide production. Indeed, using the acidic-pretreated wastewater as a fermentation medium decreased the lag phase, enhanced the growth of the strain K122 to reach a final biomass production of 20 × 10 8 cells/mL, increased culturable cell count to 262 × 10 6 cells/mL and improved oral toxicity against Ephestia kuehniella larvae by 68.4%. Among chemical pretreatments performed, the acidic hydrolysis was demonstrated to be the unique promising one for P. temperata bioinsecticide production due to its ability to reduce aromatic compounds as shown by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Graphical abstract: Image 1 Highlights: Chemical pretreatments effects on biopesticide production were investigated. Alkali and thermoalkali pre-treatments contribute to organic matter solubilization. Acidic pre-treatment was able to reduce aromatic compounds from wastewater. Acidic hydrolysis enhanced P. temperata biopesticide production.